Simultanitas dan "Trade off" Pengambilan Keputusan Financial dalam Mengurangi Konflik Agensi: Peran dari Corporate Ownership - Fuad Fuad (The Indonesian Journal of Accounting Research, 2013)
This study investigated the simultaneity of four financial variables that are hypothesized to control agency costs. It builds a model showing that debt, dividend, insider ownership, and corporate ownership are determined simultaneously as each of the variables is hypothesized to affect agency cost. This study developed the graphical analysis, as well as empirical evidences employing both Hausman specification test and three-stage least squares test. The study proved that corporate ownership was determined simultaneously by the other agency control variables, while dividend payout, debt and insider ownership were partially determined by those agency control variables. Further results, however, did not find the presence of non-linier relationship between insider ownership and all of agency control variables. Finally, this study reveals that there is a trade-off and simultaneity in the financial decision making variables to control the agency costs.